Effect of massage therapy on infants with congenital muscular torticollis: A retrospective comparative study - Wei Tang; Wei Tang; Zhoujin Li; Weihui Xu; Yong Ye; Huijuan Wang; Ying Wang; Xiangning Shao; Mengqing Wang; Jianda Xu (Frontiers Media S.A., 2023)
ObjectiveTo detect the effect and safety of massage therapy on infants with congenital muscular torticollis.MethodsA total of 56 infants with unilateral congenital muscular torticollis were enrolled in this retrospective comparative study. The subjects were divided in two groups, namely, the control group and the massage group. The control group (n = 28) received the treatment of sternocleidomastoid muscle (SCM) stretching, while the massage group (n = 28) received massage therapy combined with SCM stretching. The following parameters were compared: the cervical range of motion (ROM) and functional level (muscle function scale and ratio of muscle function scale scores). Complications, if any, were also recorded.ResultsOf the 56 infants, 7 infants (12.5%) underwent surgery with little functional improvement. The total effective rate of conservative treatment was 87.5%. No significance was found in terms of the surgery rate between both groups (14.29 vs. 10.71%, P = 0.693). After treatment, the ROM (including rotation and lateral flexion) and the ratio of muscle function scale scores improved significantly (P < 0.05). In the latest follow-up, the massage group showed a greater improvement in rotation and lateral flexion. However, no significant difference in the muscle function scale score ratio was found (P = 0.126). Importantly, no adverse events related to blood vessels, nerves, and SCM occurred.ConclusionsProviding massage therapy in infants with congenital muscular torticollis is a safe and effective method to improve the cervical range of motion and function. However, this study did not find any decrease in the surgical rate between two groups of patients despite adding such therapy.